An exploratory study of Clinical and Translational Science Award community-engaged research training programs. Issue 2 (25th June 2018) - Ziegahn, Linda; Nevarez, Lucinda; Hurd, Thelma; Evans, Jill; Joosten, Yvonne; Dumbauld, Jill; Eder, Milton "Mickey"
Abstract : Background: The Clinical and Translational Science Award (CTSA) institutions are increasing development of training programs in community-engaged research (CEnR) to support translational science. Methods: This study sampled posters at CTSA national meetings to identify CEnR training approaches, topics, and outcomes. Results: Qualitative analysis of 30 posters revealed training topics and outcomes focused primarily on CEnR capacity building, overcoming barriers, systems change, and sustainability. Conclusion: Further research should focus on development and results of CTSA CEnR training program metrics.